Mechanistic views and computational studies on transition-metal-catalyzed reductive coupling reactions. (14th November 2022) - Duan, Abing; Xiao, Fengjiao; Lan, Yu; Niu, Linbin
Abstract : Theoretical studies on transition-metal-catalyzed reductive coupling reactions have been summarized and discussed. Abstract : Transition-metal-catalyzed reductive coupling reactions have been considered as a powerful tool to convert two electrophiles into value-added products. Numerous related reports have shown the fascinating potential. Mechanistic studies, especially theoretical studies, can provide important implications for the design of novel reductive coupling reactions. In this review, we summarize the representative advancements in theoretical studies on transition-metal-catalyzed reductive coupling reactions and systematically elaborate the mechanisms for the key steps of reductive coupling reactions. The activation modes of electrophiles and the deep insights of selectivity generation are mechanistically discussed. In addition, the mechanism of the reduction of high-oxidation-state catalysts and further construction of new chemical bonds are also described in detail.